Pengaruh Inklusi Keuangan, Literasi Keuangan, Modal Usaha Dan Pemanfaatan Media Sosial Terhadap Keberlanjutan UMKM Di Jepara - Chudlori, Arif Rahman; Widiastuti, Anna (REVITALISASI : Jurnal Ilmu Manajemen, 2025)
This study aims to analyze the influence of financial inclusion, financial literacy, venture capital, and social media utilization on the sustainability of Micro, Small, and Medium Enterprises (MSMEs) in Jepara Regency. The approach used in this study is quantitative with a survey method, where data is collected through distributing questionnaires to MSME actors. The population in this study is all MSME actors in Jepara Regency, totaling 81,909 business units. The sampling technique used random sampling, and the number of samples is determined using the Slovin formula with a 10% error rate, resulting in 100 respondents. Data analysis was carried out using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method. The results show that all independent variables, namely financial inclusion, financial literacy, venture capital, and social media utilization, have a positive and significant effect on the sustainability of MSMEs. This finding supports the Resource-Based View (RBV) theory, which states that optimal management of internal resources can increase competitiveness and business continuity. This research offers practical implications for MSMEs and local governments to strengthen access to financial services, improve financial literacy capacity, and utilize digital technology to support business sustainability. This study has limitations in coverage and sample size, so it is recommended that future research expand the population and consider a mixed-method approach to obtain more comprehensive results.